The effects of adding amaranth spinach (Amaranthus spp) on nugget tofu nuggets’ nutritions and organoleptics - Alfiatur Rahmi; Wiqayatun Khazanah (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
The use of amaranth spinach to increase the nutritional values in a food is considered beneficial for health. To date, tofu dregs are considered waste and underestimated because they are only used as manure. An alternative to process tofu dregs is making tofu dreg nuggets. This study aimed to determine the effects of adding 100 g, 200 g, and 300 g amaranth spinach on the organoleptic and chemical properties of tofu nuggets. This study used an experimental design. The organoleptic test was conducted at the Unggul Lampeunerut Elementary School, and the test was conducted at the Laboratory of Nutrition Science and Food Technology, Universitas Syiah Kuala, Banda Aceh. The analysis of variance found that the tofu dreg nuggets’ color earned the highest average value of 3.65. Meanwhile, the highest average values of the aroma, taste, and texture were 3.74, 3.70, and 3.82, respectively. The highest average values of protein, crude fiber, and water were 5.99, 4.71, and 52.80, respectively. Moreover, this study revealed that adding different amounts of amaranth spinach to nuggets significantly affected the organoleptic values of colors, aromas, tastes, and textures. However, this addition did not significantly affect the chemical content of tofu nuggets, such as protein, crude fiber, and water. Further research should investigate the addition of other material compositions to tofu dreg nuggets because the chemical characteristics of tofu dregs nuggets in this study are still below the SNI standard.